Determinan Audit Fee Pada Badan Usaha Milik Negara Tahun 2022-2024 - Nirmalasari, Yusrina; Zaky, Achmad (Disclosure: Journal of Accounting and Finance, 2026)
This study aims to examine the relationship between audit fees in Indonesian state-owned enterprises (SOEs), audit committee size, business complexity, company size, and public accounting firm size. This analysis uses only SOEs officially registered on the SOE website. Annual reports and financial statements covering 2022–2024 are among the secondary sources used to collect data. The analytical method used is panel data regression. Hypotheses are tested using multiple linear regression after model selection and classical assumption testing. Audit fees are not affected by audit committee size or firm complexity. Audit fees are found to be higher for larger organizations and those with higher PAF. These results indicate that audit fees in SOEs are not always determined by the level of company complexity or the existence of an audit committee. Business size and the credibility and competence of the public accounting firm have a more significant impact on audit fees. Due to broader audit coverage, larger transaction volumes, and higher professional risk faced by auditors, large companies and the size of the public accounting firm often charge higher audit fees.